Studi Kasus Siswa Yg Mengalami Keterlambatan Membaca di Desa Karya Jadi Kecamatan Batang Serangan - Alfin Siregar; Anjani Farras Arifany; Nikene Sampin; Putri Evita Sari Nst; Vera Yuliza (Jurnal Ilmiah Wahana Pendidikan, 2023)
Learning is a process of making humans better. Learning at school seems to have not succeeded in overcoming the learning difficulties experienced by students. Approximately 85% of children are declared with language difficulties. The role of the teacher must be able to plan learning in reading well so that students are able to become a habit as something very interesting, and can create through language games in teaching reading to students. This article aims to find out cases of late reading in grade VI elementary school students and the factors that cause reading delays in Karya Jadi Village, Batang Serangan District. This research uses a descriptive qualitative method with a case study approach. The data collection technique used was data collected from various sources and the results of this study were only applicable to the cases investigated indicating that reading delays were due to a lack of interest in reading in sixth grade students of SD in Karya Jadi Village in a low sense. From the level of student access to the library, very few do. Students cannot read because they do not have knowledge of reading letters. Factors that affect students' reading delays are: internal and external factors of students